2023
DOI: 10.1039/d3bm00306j
|View full text |Cite
|
Sign up to set email alerts
|

Macro-microporous ZIF-8 MOF complexed with lysosomal pH-adjusting hexadecylsulfonylfluoride as tumor vaccine delivery systems for improving anti-tumor cellular immunity

Abstract: Tumor vaccine therapy, which can induce tumor antigens-specific cellular immune responses to directly kill tumor cells, is considered to be one of the most promising tumor immunotherapies. How to elicit...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Studies have reported that efficient endo –lysosomal escape of an antigen can promote antigen cross-presentation to greatly improve MHC-I presentation for CD8 + T cells priming. 35 Thus the ability of MIL-BC@PAA to effect cytosolic delivery was clarified on BMDCs using confocal microscopy. Almost all the red (antigen) and green fluorescence (lysosomal) signals overlapped at 1 h incubation, and nearly negligible discrete fluorescence signal could be seen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that efficient endo –lysosomal escape of an antigen can promote antigen cross-presentation to greatly improve MHC-I presentation for CD8 + T cells priming. 35 Thus the ability of MIL-BC@PAA to effect cytosolic delivery was clarified on BMDCs using confocal microscopy. Almost all the red (antigen) and green fluorescence (lysosomal) signals overlapped at 1 h incubation, and nearly negligible discrete fluorescence signal could be seen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of this study, ZIF-8 nanoparticles served as an instrumental drug carrier for precise and targeted delivery in the realm of cancer therapy. 23,114–122…”
Section: Utilizing Zif-8 For Targeted Delivery Of Pd-l1 In Immunotherapymentioning
confidence: 99%
“…In the evolving landscape of the biomedical field, strategies including chemotherapy, photodynamic therapy, photothermal therapy, chemical dynamic therapy, and combination therapy have demonstrated significant potential in cancer treatment. ,, However, these approaches remain challenges in clinical implementation, including nonspecific distribution and unfavorable pharmacokinetics, resulting in undesirable high doses and causing toxicity to the body. Many research suggests that NMOFs and NCPs are highly promising nanocarriers for delivering therapeutic agents to the tumor sites. ,, This provides a means to achieve enhanced therapeutic effects at low doses.…”
Section: Nmofs and Ncps For Cancer Therapymentioning
confidence: 99%